THE IMPLEMENTATION OF “SHADOWING” AS A TECHNIQUE IN TEACHING LISTENING OF A PROCEDURE TEXT TO THE ELEVENTH GRADERS (RETAIN, 2017)
THE IMPLEMENTATION OF “SHADOWING” AS A TECHNIQUE IN TEACHING LISTENING OF A PROCEDURE TEXT TO THE ELEVENTH GRADERS Mochamad Arman Firmansyah Engish Literature, Faculty of Language and Arts, The State University of Surabaya Arman_firmansyah@rocketmail.com Dr.Oikurema Purwati, Eng. Grad. Dip, M.Appl. English Literature, Faculty of Language and Arts, The State University of Surabaya Pungki_unesa@yahoo.co.id Abstrak Dimasa sekarang kebanyakan murid murid lebih suka melakukan aktivitas listening daripada speaking, reading dan writing. Tapi nyatanya listening adalah pekerjaan yang paling susah untuk murid murid. Berdasarkan masalah ini, pendidik dianjurkan untuk mencari strategi yang cocok agar para murid muridnya mampu melakukan kegiatan listening. Untuk mengatasi masalah tersebut, ada sebuah teknik bernama “shadowing” yang mampu membantu pendidik untuk mengembangkan pemahaman listening para murid muridnya tersebut. Untuk mengenal lebih tentang teknik ini, penulis melakukan penelitian tentang bagaimana teknik ini digunakan dalam mengajar teks prosedur dikelas listening pada murid kelas 11 dan penulis juga ingin mengetahui respon dari murid murid terhadap teknik ini. Penulis menggunakan deksriptif kualitatif sebagai desain risetnya. Ceklist observasi dan interview dipilih untuk pengambilan data dari dua kali pertemuan riset tersebut. Penulis mengobservasi proses belajar mengajar dikelas dan juga menginvestigasi hasilnya dengan melakukan wawancara dengan para murid. Setelah mengumpulkan dan memperoleh semua data dari riset tersebut, penulis lalu melakukan analisa terhadap hasil tersebut untuk mendapatkan hasil dari riset tersebut. Hasil dari penelitian ini menunjukan bahwa pendidik menggunakan teknik ini dengan mengaplikasikanya kedalam tiga fase dalam listening yaitu pre-listening, whilst-listening, dan post-listening dan itu berhasil diaplikasikan berdasarkan 4 fase dalam shadowing yaitu mendengarkan suara rekaman, shadowing, pengecekan pemahaman, dan aktivitas pengosakataan. Para murid mampu mengerjakan tugas yang diberikan oleh guru dan sukses memahami isi dari rekaman, respon dari murid murid menunjukkan bahwa teknik ini membantu mereka untuk mengerjakan latihan latihan listening lebih baik daripada sebelum mereka mengenal teknik ini, lebihnya mereka ingin menggunakan teknik ini dalam menghadapi kegiatan listening. Dari hasil diatas penulis menyimpulkan bahwa teknik ini membantu murid murid dalam menghadapi tugas listening dan juga mampu mengembangkan pemahaman mereka terhadap rekaman suara tersebut. Kata Kunci : Teknik “shadowing”, listening, teks prosedur. Abstract Nowadays many students tend to do listening activity rather than speaking, reading and writing but the fact listening is the most difficult task for the students. Based on this problem, teacher need to find a proper strategy to make their students able to do listening task. To overcome that problem, there is a technique called “shadowing” which help the teacher to improve their student’s listening comprehension. In order to know more about this technique, the writer conduct a research about how this technique applied in teaching listening of a procedure text to the eleventh graders students and the writer also wants to know the student’s response toward this technique. The writer use descriptive qualitative research as a research design to this study. Observation checklist and interview have been choose in order to collecting the data of the two meetings of this study. The writer observed the teaching and learning process in the class and also investigated the result by doing an interview to the students. After collecting and gathering all data from this study, the writer then analyzed them in order to get the result of this study. The result of this study shows that the teacher implemented this technique by applying this technique on three phases of listening those are pre-listening, whilst-listening, and post-listening and successfully applied this technique based on the phases of shadowing those are listen to the passage, shadowing, comprehension checking, and vocabulary activity. The subject could do the exercise which given by the teacher and successfully understand the audio. The student’s response show that this technique helps them to do the listening exercise or task better than before they know this technique. Furthermore they want to use this technique to face the listening activity. From the result above the writer concluded that this technique helps the students in facing their listening task or exercise and also it is improving their understanding of the audio. Keywords :“shadowing” technique, listening, procedure text.